ANALYSIS OF FINANCIAL RATIOS TO MEASURE THE FINANCIAL PERFORMANCE OF THE WEST SUMBAWA REGENCY REGENCY - Janna, Ilza Lail Fatul; Syafinah, Shofyah; Hustin, Yunia Yunara; Agustin, Verren Regina; Puspawati, Sumarni (Jurnal Ilmu Ekonomi, 2022)
Analysis of financial ratios to the Regional Revenue and Expenditure Budget (APBD) is one of the parameters in measuring the performance of regional financial management. Analysis of financial performance uses the calculation of the ratio of effectiveness, efficiency and regional financial independence. This study aims to measure the financial performance of the Regional Government of West Sumbawa Regency for the 2019 – 2021 Fiscal Year. The type of research used is quantitative descriptive using ratio analysis methods. The results showed that the effectiveness ratio was categorized as very effective, the efficiency ratio was categorized as inefficient, and the regional financial independence ratio was categorized as very low. It is hoped that the Regional Government of West Sumbawa Regency can further increase PAD, and optimize the acquisition of PAD through exploring new regional income sources.